APT – Kohdistettu hyökkäys - Kuhalampi, Matti (2018)
The number of cyberattacks have been increasing for a long time. In addition to this, especially in ongoing decade cyberattacks have become better resourced, more advanced and more precisely targeted than before. The goal of these attacks is mainly stealing high value data to gain financial or political advantage for example. Usually the perpetrators behind these attacks are different kinds of groups, organisations and even nations. These kind of attacks go by the term “APT“, which stands for advanced persistent threat. This paper tries to answer the question: What is APT and is it possible to stay safe from it? There is no single pivotal matter in defending against an APT but penetration testing, employees’ threat awareness and outbound traffic monitoring proved their significance.